Artificial intelligence in providing the first and second signal systems with polysensory information for precise coordination of volleyball players actions - Khaupshev M.Kh.; Bazhev A.Z.; Khezhev A.A.; Bazhev A.A. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to justify the use of artificial intelligence in managing the process of precise coordination of the actions of volleyball players. Methods and structure of the study. The scientific work used the technology of planning and monitoring the dynamics of development of the accuracy of coordination of the components of the first and second signal systems, the success of technical and tactical actions of volleyball players in training and competition conditions. Results and conclusions. It was established that the use of artificial intelligence as a technology for managing the educational process in volleyball made it possible to create conditions for variability and increase the coordination of functional and motor systems; develop coordination abilities in leading sensory systems; stimulate the development of cognitive and intellectual qualities, accompanying the actions with objective and urgent information of the second signaling system; ensure an effective increase in the accuracy of technical and tactical actions and competitive game tension.